New Methodology for Chattering Suppression of Sliding Mode Control for Three-phase Induction Motor Drives - Sulaiman , Marizan; Patakor, Fizatul Aini; Ibrahim, Zulkifilie (World Scientific and Engineering Academy Society, 2014)
Chattering is undesirable phenomenon when dealing with sliding mode control. This paper proposed a new method for addressing chattering with a simple and easy implementation in Digital Signal Processor (DSP). This is realized by replacing the discontinuous function in conventional sliding mode control with statedependent auto-tuning of boundary layer in fast sigmoid function and state-dependent switching gain, for threephase induction motor speed control. This method allows chattering reduction in control input, while keeping the robustness characteristics of sliding mode control. The performance of the proposed control is verified in emulation induction motor drives using Digital Signal Processor TMS320F2812 board, with different speed command and load disturbances.